Interface compatibility and mechanisms of improved mechanical performance of starch/poly(lactic acid) blend reinforced by bamboo shoot shell fibers. Issue 35 (29th April 2019) - Guan, Mingjie; Zhang, Zhiwei; Yong, Cheng; Du, Keke
ABSTRACT: Bamboo shoot shell fibers (BSSFs)/starch/poly(lactic acid) (PLA) ternary composites were prepared by blending BSSFs to starch/PLA matrices for the purpose of expanding BSSFs applications to enhance starch/PLA composites and creating a new low‐cost biodegradable composite. The effects of BSSFs content (0–40 wt %) on the physical–mechanical properties were tested and interface compatibility and its mechanism to mechanical performance of BSSFs/starch/PLA composites were characterized by SEM‐EDS, TG. The results showed that the mechanical strength, surface wettability, and water absorption of the composites continued improving when the BSSFs content increased from 0% to 20 wt %. However, mechanical modulus increased with increase in BSSFs content. The results of fracture microstructure and thermal property exhibited a good interfacial compatibility at low content of BSSFs and an interface debonding at high content of BSSFs. These investigations indicated that the BSSFs reinforcement to the composite is not consistent with interface compatibility of the ternary composites. The composites should be considered as a kind of green and low‐cost biodegradable materials to replace traditional single‐phase or multiphase materials. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47899. Abstract :